Socialization, Knowledge,Understanding, And The Complexity Of Tax Administration Towards The Use Of Tax Incentives During A Pandemic - Umi Nandiroh; Irma Hidayati (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2022)
The Covid-19 virus has greatly impacted people's lives. It not only attacks human health but also other sectors, especially in the economic sector. The government has made various efforts to overcome the COVID-19 outbreak. One of them is the restriction of community activities in public to avoid crowds. It is done to slow down the rate of COVID-19 virus transmission. This policy has changed the social order and impacted various sectors. The learning process, worship, and the trading transaction is shifting from offline to online. The government continues trying to restore the community's economy, one of which is in the MSMEs sector, where it has an essential role in maintaining the national economic stability. Therefore, the government supports the recovery by issuing the Minister of Finance Regulation Number 82/PMK.03/2021, the regulation which regulates the amendment to PMK-9/PMK.03/2021 extends the period of providing incentives until December 2021. However, the tax incentives utilized by MSMEs have not reached the target. By using a questionnaire, the collected data were analyzed using multiple linear regression. It was found that knowledge and understanding, as well as the complexity of tax administration, positively affect the Utilization of tax incentives. Meanwhile, socialization does not affect the use of tax incentives. In fact, although the Directorate General of Taxation (DGT) has conducted socialization, the Utilization of tax incentives by MSMEs is far behind the target.